2021
DOI: 10.1155/2021/6646588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on the Mechanical Properties of a 3 mm Commercially Pure Titanium Plate (CP-Ti Grade 2)

Abstract: Titanium is seen as a good material for application in many fields due to its compatibility with different environments. However, it remains unclear whether what happens when this material is exposed to certain high temperatures for longer periods of time. The primary objective of this study was to investigate the effect of heat on a 3 mm commercially pure titanium grade 2 plate at a constant temperature of 900°C at different heating times. Three different heating times were employed in this study: 30 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Increasing the hardness of jaw implants can refer to basic material science, where the heat treatment process can be used to increase the hardness of a material (Callister and Wiley, 1980). The effect of the heat treatment process has been widely studied on titanium materials (da Rocha et al, 2006;Venkatesh, Chen and Bhole, 2009;Reda, Nofal and Hussein, 2013;Catherine and Hamid, 2018;Arab, Chen and Guo, 2019;Mpumlwana, Msomi and Fourie, 2021;Jian et al, 2022). Reda, et al, have investigated the effect of single and duplex stage heat treatment (SSHT and DSHT) on the material hardness of the titanium alloy cast (Reda, Nofal and Hussein, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the hardness of jaw implants can refer to basic material science, where the heat treatment process can be used to increase the hardness of a material (Callister and Wiley, 1980). The effect of the heat treatment process has been widely studied on titanium materials (da Rocha et al, 2006;Venkatesh, Chen and Bhole, 2009;Reda, Nofal and Hussein, 2013;Catherine and Hamid, 2018;Arab, Chen and Guo, 2019;Mpumlwana, Msomi and Fourie, 2021;Jian et al, 2022). Reda, et al, have investigated the effect of single and duplex stage heat treatment (SSHT and DSHT) on the material hardness of the titanium alloy cast (Reda, Nofal and Hussein, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure(600s) of the titanium alloy to the aging temperature above 200 °C resulted in a complete loss of ductile property with increased yield stress value up to 1300 MPa. Mpumlwana et al [12] reported that mechanical properties of Ti-6Al-4V alloy had been significantly affected by heat-treatment duration. The authors tested the alloys at a constant temperature of 900 °C for different durations such as 30 min 60 min, and 90 min.…”
Section: Introductionmentioning
confidence: 99%
“…Annealing reduces tensile strength but improves the ductility of the titanium alloy (Mpumlwana et al , 2021). This change in tensile properties is due to the decomposition of α' into α + β microstructure and grain-growth expressed by the Hall–Petch relationship, according to which as grain size increases, tensile strength decreases (Davari et al , 2017).…”
Section: Introductionmentioning
confidence: 99%